2018
DOI: 10.1007/s10903-018-0800-z
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Patterns in Chinese Americans are Associated with Cardiovascular Disease Risk Factors, the Chinese American Cardiovascular Health Assessment (CHA CHA)

Abstract: Little is known about the dietary patterns of Chinese Americans. Understanding their dietary patterns can provide insights for addressing cardiovascular disease (CVD) risk among Chinese American immigrants. The objective of this study was to identify dietary patterns among Chinese American immigrants living in New York City (NYC) and to describe associations with demographic and CVD risk factors. A validated Food Frequency Questionnaire assessed usual dietary intake in Chinese American immigrants living in NYC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…Three of these studies focused on Chinese women exclusively [ 35 , 48 , 50 ]. Ten (10/51, 19.6%) studies reported that Chinese immigrants in Canada and the United States had a lower daily caloric intake than Caucasians [ 8 , 19 , 21 , 28 , 32 , 34 , 54 , 61 , 63 , 65 ]. Caloric consumption was reported by two studies at 1592 kcal/day and 1736 kcal/day [ 8 , 34 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Three of these studies focused on Chinese women exclusively [ 35 , 48 , 50 ]. Ten (10/51, 19.6%) studies reported that Chinese immigrants in Canada and the United States had a lower daily caloric intake than Caucasians [ 8 , 19 , 21 , 28 , 32 , 34 , 54 , 61 , 63 , 65 ]. Caloric consumption was reported by two studies at 1592 kcal/day and 1736 kcal/day [ 8 , 34 ].…”
Section: Resultsmentioning
confidence: 99%
“…Ten (10/51, 19.6%) studies reported that Chinese immigrants in Canada and the United States had a lower daily caloric intake than Caucasians [ 8 , 19 , 21 , 28 , 32 , 34 , 54 , 61 , 63 , 65 ]. Caloric consumption was reported by two studies at 1592 kcal/day and 1736 kcal/day [ 8 , 34 ]. The dietary quality of Chinese immigrants was found to be 66.2/110 on the AHEI score, a scale for which values above 80 indicates a good diet and lower than 50 indicates a poor diet [ 19 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among limitations of our study, our restriction to health-seeking subjects may not be generalisable to other populations. Nevertheless, our data may be relevant to health inequalities in Chinese populations in North America [ 53 56 ], United Kingdom [ 57 ] and Australia [ 58 ] in whom first- or even second-generation Chinese immigrants may still prefer their native language. Language preferences for Malay and Indian ethnicities were not elicited in our study, because of the small number of participants in these groups.…”
Section: Discussionmentioning
confidence: 99%
“…Acculturation can increase disease risk because immigrants tend to increase their consumption of fats, sweets, and soft drinks (Pan et al 1999;Lv and Cason 2004), which then increases risk of obesity and cardiovascular disease (Beasley et al 2018). Increased consumption of western and reduced consumption of traditional Chinese foods was commonly reported by Chinese immigrants to the United States (Lv and Cason 2004) necessitated by low availability of affordable traditional Chinese foods (Satia et al 2000).…”
Section: Introductionmentioning
confidence: 99%